The Neuroprotective Effect of the Association of Aquaporin-4/Glutamate Transporter-1 against Alzheimer’s Disease - Yu-Long Lan; Shuang Zou; Jian-Jiao Chen; Jie Zhao; Shao Li (Neural Plasticity)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that is characterized by memory loss and cognitive dysfunction. Aquaporin-4 (AQP4), which is primarily expressed in astrocytes, is the major water channel expressed in the central nervous system (CNS). This protein plays an important role in water and ion homeostasis in the normal brain and in various brain pathological conditions. Emerging evidence suggests that AQP4 deficiency impairs learning and memory and that this may be related to the expression of glutamate transporter-1 (GLT-1). Moreover, the colocalization of AQP4 and GLT-1 has long been studied in brain tissue; however, far less is known about the potential influence that the AQP4/GLT-1 complex may have on AD. Research on the functional interaction of AQP4 and GLT-1 has been demonstrated to be of great significance in the study of AD. Here, we review the interaction of AQP4 and GLT-1 in astrocytes, which might play a pivotal role in the regulation of distinct cellular responses that involve neuroprotection against AD. The association of AQP4 and GLT-1 could greatly supplement previous research regarding neuroprotection against AD.